Peningkatan Pemahaman Siswa Kelas V UPT SDN 30 Koto Tuo tentang Perbedaan Zakat, Infak, Sedekah, Wakaf, dan Hadiah melalui Penggunaan Video Pembelajaran - Betri Herman (Jurnal Pendidikan Tuntas, 2024)
This study aims to improve the understanding of grade V students of UPT SDN 30 Koto Tuo about the differences between zakat, infaq, sadaqah, waqf and gifts through the use of learning videos. The problem faced is the lack of student understanding of these concepts which are very important in social and religious life. The method used in this research is classroom action research (PTK) with a cycle consisting of planning, implementation, observation, and reflection. During the implementation of the action, students were given material about zakat, infaq, sadaqah, waqf, and gifts using learning videos that were designed in an interesting and interactive way. The results showed that the use of learning videos can improve students' understanding of the differences between the five concepts. This is evidenced by the increase in the average score of student comprehension tests before and after the use of learning videos. This study suggests that learning videos be used as an alternative in the learning process to improve students' understanding of the material taught.